أبعاد رأس المال الفكري ومكوناته ودروه في الجامعات:دراسة وصضية تحليلية - Khatijah Binti Othman; Musallam Said Musallam Hardan (Islamic Research Society, 2024)
This descriptive study discusses the impact of intangible assets, ie, intellectual capital, in generating revenues for organizations, as they contribute to the generation of new knowledge, and that they can be used for multiple and simultaneous use. The problem of the study is the weak contribution of intellectual capital to universities in the sustainable development of educational institutions. This may be attributed to the lack of benefit from the contribution of academics, whether from research recommendations, as confirmed by the results of many studies. The objectives of the study are explaining evolution and dimensions of the intellectual capital, discussing intellectual capital in the Islamic perspective, and discussing the reality of intellectual capital in universities. The descriptive analytical approach was discussed in three sections. The outputs referred to a set of results. The most important of these is that intellectual capital is a modern subject, and there is still ambiguity, debate and debate, in the absence of a specific agreed concept for this term. It is a competitive advantage in the Organization and a source of wealth for the Organization. The treatment of Islam with intellectual capital, we find in the book of God that intellectual capital stems from the owners of minds and dogs in the Holy Quran, when these words mentioned in (٦١) verse distributed in (٤٣) Surat Karima. The interest of universities in intellectual capital is necessary to face competition between institutions of higher education, and the pursuit of the majority of universities to maximize their economic returns.